2013
DOI: 10.1103/physrevb.88.085109
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium transport of helical Luttinger liquids through a quantum dot

Abstract: We study a steady state non-equilibrium transport between two interacting helical edge states of a two dimensional topological insulator, described by helical Luttinger liquids, through a quantum dot. For non-interacting dot the current is obtained analytically by including the self-energy correction to the dot Green's function. For interacting dot we use equation of motion method to study the influence of weak on-site Coulomb interaction on the transport. We find the metal-to-insulator quantum phase transitio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 41 publications
2
19
0
Order By: Relevance
“…Increasing the repulsive interaction strength leads to the suppression of the differential conductance on resonance and shifts the weight away from resonance. This feature is similar to the case of two Luttinger leads connected by a noninteracting quantum dot 36 with particle hole-symmetric bias voltage (µ 1 = −µ 2 = eV /2).…”
Section: Discussionsupporting
confidence: 70%
“…Increasing the repulsive interaction strength leads to the suppression of the differential conductance on resonance and shifts the weight away from resonance. This feature is similar to the case of two Luttinger leads connected by a noninteracting quantum dot 36 with particle hole-symmetric bias voltage (µ 1 = −µ 2 = eV /2).…”
Section: Discussionsupporting
confidence: 70%
“…For the fermionic environment we consider the setup of a quantum wire [17,18] tunnel coupled to superconducting wires as shown in figure 1. We take the helical Luttinger wire [48], which can be realized as the edge state of some two-dimensional topological insulator [46], as a special example, but the generalization to other kinds of Luttinger liquids [47] is straightforward. For the bosonic environment we take the ring structure [19], as shown in figure 2, with external magnetic flux Φ controlling different frequency modes of bosonic couplings.…”
Section: Decoherence Patterns Of Topological Qubitsmentioning
confidence: 99%
“…The above picture of a quantum phase transition might be understood via the renormalization group (RG) argument for the coupling constant B M . Note that the fermionic environment that we choose in this paper is the helical Luttinger liquids, which can be realized as interacting edge states of two-dimensional topological insulators [46,48]. For this kind of fermionic environment, the scaling dimension from zeroth-order renormalization group analysis [48,49] for the interaction V is κ.…”
Section: The Environmental Influence Function Of Helical Luttinger LImentioning
confidence: 99%
See 1 more Smart Citation
“…A feasible possibility is the application of local potentials to form quantum antidots. More generally, the presence of constrictions in two-dimensional topological insulators have been proposed to give rise to coherent oscillations [18], transformations between ordinary and topological regimes [19], peaks of noise correlations [20], metal-to-insulator quantum phase transitions [21], nonequilibrium fluctuation relations [22], braiding of Majorana fermions [23], competition between Fabry-Pérot and Mach-Zehnder processes [24], control of edge magnetization [25], and detection of Kondo clouds [26]. Interestingly, König et al have experimentally demonstrated [27] the local manipulation of helical states with back-gate electrodes.…”
Section: Introductionmentioning
confidence: 99%